2021
DOI: 10.1177/03015742211016595
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Infrazygomatic Bone Thickness With Cervical Vertebrae Maturation Stages

Abstract: Anchorage is one of the most important consideration in the field of orthodontics to achieve a desired tooth movement. In order to eliminate the undesirable side effects such as anchorage loss, skeletal anchorage systems such as mini-implants have been introduced in orthodontics. Aim: To evaluate the bone thickness of the infrazygomatic crest in different cervical vertebrae maturation index (CVMI) and to compare it between male and female subjects, by using cone beam computerized tomography (CBCT) imaging. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(38 reference statements)
0
0
1
Order By: Relevance
“…However, with research Murugesan et al 28 and Amri et al 29 showed similar results and recommended that at a height of 12 to 17 mm from the occlusal plane with an insertion angle of 65 to 70 degree, 9 to 11 mm implants must be used. 30 Concerning the present study by Krishnakumaran et al (2021) 30 the superolateral region of infrazygomatic bone is thickest with the maximum mean bone thickness of 10 mm at zygomatic process of maxilla while the anterior wall of maxillary sinus was thinnest with the maximum mean bone thickness of 5 mm in the completion stage of CVMI i.e., bone density increases with advancing age.…”
Section: Discussioncontrasting
confidence: 41%
“…However, with research Murugesan et al 28 and Amri et al 29 showed similar results and recommended that at a height of 12 to 17 mm from the occlusal plane with an insertion angle of 65 to 70 degree, 9 to 11 mm implants must be used. 30 Concerning the present study by Krishnakumaran et al (2021) 30 the superolateral region of infrazygomatic bone is thickest with the maximum mean bone thickness of 10 mm at zygomatic process of maxilla while the anterior wall of maxillary sinus was thinnest with the maximum mean bone thickness of 5 mm in the completion stage of CVMI i.e., bone density increases with advancing age.…”
Section: Discussioncontrasting
confidence: 41%